2015
DOI: 10.1111/liv.12911
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of autochthonous acute hepatitis E with short‐term ribavirin: a multicenter retrospective study

Abstract: Treatment of acute HEV infection using ribavirin seems safe and effective. Short-term treatment tailored to viraemia may be the best regimen for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 16 publications
0
47
1
1
Order By: Relevance
“…Patients with acute hepatitis E and underlying chronic liver disease have a poor prognosis, and a small number of such patients have been treated successfully with ribavirin [34] . Patients with chronic infection (defined as persisting viremia >3 months) should be treated.…”
Section: Detection Prevention and Treatment Of Hepatitis Ementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with acute hepatitis E and underlying chronic liver disease have a poor prognosis, and a small number of such patients have been treated successfully with ribavirin [34] . Patients with chronic infection (defined as persisting viremia >3 months) should be treated.…”
Section: Detection Prevention and Treatment Of Hepatitis Ementioning
confidence: 99%
“…Those who present late will often display patterns of liver enzyme derangement indistinguishable from those seen in other causes of acute-on-chronic liver failure [32] . Early intervention with ribavirin has been shown to have efficacy in treating these patients [34] , and so routine testing for HEV should be considered for all individuals presenting with decompensated chronic liver disease.…”
Section: Acute Infectionmentioning
confidence: 99%
“…In contrast, autochthonous HEV infection usually presents with a milder course of disease (7) and is only sporadically reported as the cause of decompensation and ACLF in large Western cohorts (19). A retrospective cohort of patients treated with ribavirin for autochthonous HEV infection revealed that mortality occurred only in patients with acute decompensation of underlying cirrhosis (20). It cannot be excluded that other hepatic or extrahepatic factors might have contributed to the decompensation of cirrhosis in the current study patient (21).…”
mentioning
confidence: 86%
“…It remains elusive whether treatment with ribavirin would have ameliorated the course of ACLF and prevented acute pancreatitis as an extrahepatic manifestation. However, the severe course of HEV infection in elderly patients with underlying liver disease evidence supports the early use of ribavirin in patients at risk (20).…”
Section: Aclf Gradementioning
confidence: 99%
“…A few patients who have presented with severe acute HEV infection, or acute or chronic hepatitis, have been given ribavirin [40,41]. A rapid decrease in HEV RNA concentration has been obtained and HEV clearance achieved.…”
Section: Treatment Of Hev Infection With Additional Complicationsmentioning
confidence: 99%